Feasibility of Cement Mortar System with Industrial Metal Fibre Waste - Perera, K.D.Y.G.; Ahamed, Y.L.F.; Somarathna, H.M.C.C (University of Jaffna, 2022)
The traditional cement mortar has limited characteristics. Because of the lack of expected results, the engineering scope has focused on alternative materials instead of using the traditional constituents. As a result of that different types of fibres have been used in the past. In addition, the electrical distribution cables no longer operate for power transmission purposes when the length is not adequate and after it reaches its’ end of life and the disposal methods are not eco-friendly. Therefore, the purpose of the study was to evaluate the feasibility of cement mortar with the metal fibre waste which was extracted from electrical distribution cables. 1.35 mm diameter aluminium fibres were used by changing their volume ratio at four levels 0.5%, 1.0%, 1.5%, and 2.0%. Wet and dry density and compressive tests were mainly carried out to determine the behaviour of the developed mortar systems. The wet, dry densities and modulus of elasticity were increased with the fibre addition. The maximum compressive strength of the MFRM was increased respect to reference mortar by 19.7% (3rd day), 19.8% (7th day), 11.7% (28th day dry) and 25% (28th day wet). The overall results of the study emphasized the mortar mix with 1.5% of fibres performed well in all mechanical tests and also it showed.
Keywords: Metal waste fibre; Fibre reinforced mortar; Waste management; Sustainability